The Cloze Procedure A Selected Annotated Bibliography - Riley, Pamela M., Comp. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The material included in this annotated bibliography has been arranged in several categories: general references to cloze procedure; methodology and rationale of cloze; cloze as a measure of readability, including cloze as a criterion to establish readability levels and as a predictor of achievement; cloze as a teaching technique; cloze in English as a second language; cloze in languages other than English; and other studies. The section on cloze and English as a second language includes research that has been completed in Australia, the Pacific, and Asia, as well as in the United States. Also included in this bibliography are studies with handicapped subjects. (WR)
Availability: Joanne McClarty, Papua New Guinea University of Technology, P. O. Box 793, New Guinea.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Cloze Procedure; Readability; Reading; Reading Ability; Reading Achievement; Reading Comprehension; Reading Instruction; Reading Research; Reading Skills; Reading Tests; Teaching Methods; Reference Materials, Bibliographies